EFFECTIVE ISLAMIC EDUCATION METHODS IN INCREASING SPIRITUAL INTELLIGENCE - Cahyo Widodo; Husna Nashihin; M. Sulthon Adi Pramono (Proceeding of International Conference of Islamic Education, 2025)
This study aims to examine effective Islamic education methods in improving students' spiritual intelligence. Spiritual intelligence is seen as an important dimension in the formation of a complete Islamic character and personality. This study uses a qualitative approach with a library research method, where data is obtained through a review of various literature sources in the form of books, national and international journals that are relevant to the research topic. Data analysis techniques are carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that effective Islamic education methods in improving spiritual intelligence include the exemplary method (uswah hasanah), habituation of worship, internalization of Qur'anic and hadith values, and reflective dialogue that builds students' spiritual awareness. The application of these methods in an integrated manner in the learning process is able to foster spiritual intelligence that is reflected in religious attitudes, self-awareness, social empathy, and good self-control. The conclusion of this study is that the success of developing spiritual intelligence is greatly influenced by the synergy between teacher exemplary behavior, a conducive educational environment, and a curriculum that integrates cognitive, affective, and psychomotor aspects in a balanced manner.